Caracterização estrutural do fator de crescimento de fibroblasto-10 (FGF-10) e seu papel na fisiologia folicular ovariana - Chaves, Roberta Nogueira; Lima, Isadora Machado Teixeira; Duarte, Ana Beatriz Graça; Buratini Jr., José [UNESP]; De Figueiredo, José Ricardo (My University, 2011)
Background: Interest in folliculogenesis has grown extensively in recent years. Nevertheless, several aspects of follicular activity are still poorly understood. Thus, in vitro culture of ovarian follicles using new substances has been established as a very viable model, enhancing the prospects for a better understanding of follicular activity. Among the family members of the fibroblast growth factor (FGFs), FGF-10 has received recent attention for its ability to regulate the development of ovarian follicles and oocyte maturation. Given the relevance of FGF-10 in the folliculogenesis process, this review aimed to describe the structural features, expression and the main biological effects of FGF-10 on the development of ovarian follicles in mammals. Review: Along this work, it was shown aspects related to structural characterization of FGF-10 and its receptors, as well as FGF-10 expression in different cell types, emphasizing its importance to follicular development. FGF-10 is a paracrine member of the family of FGFs, and is characterized by promoting biological responses via cell surface receptors (FGFRs) of tyrosine kinase-type. Of these receptors, FGFR-1, FGFR-2 and FGFR-3 may undergo alternative transcriptional arrangements, enabling the formation of two isoforms (b and c) that have varying degrees of affinity for the various FGFs. Thus, seven FGFR proteins (FGFRs 1b, 1c, 2b, 2c, 3b, 3c and 4) with different binding specificities are generated from the four FGFR genes. The FGFRs transmit intracellular signals after binding with the ligand through the phosphorylation of tyrosine, which activates various transduction patterns in the cytoplasm. The signal transduction of FGF-10 may occur through three main pathways: protein of rat sarcoma (Ras)/MAPK, PLCγ/Ca 2+ and phosphatidylinositol-3 kinase (PI3K)/ protein kinase B (Akt), which are involved in the transmission of biological signals, leading to cellular proliferation and differentiation. FGF-10 mRNA expression was detected in the ovarian stroma, oocyte and theca cells of preantral and antral follicles. On the other hand, the expression of mRNA for FGF-10 receptors was found in, granulosa cells, theca cells, cumulus cells and oocytes. Although FGFs are widely distributed in different tissues and cell types, the importance and function of FGFs in the ovary are still poorly documented. FGF-10 has been shown to be an important mediator of mesenchymal and epithelial cell interactions during follicle development, promoting follicular survival, activation and growth. Besides the action on folliculogenesis, FGF-10 was recently identified as a growth factor able to improve oocyte competence. However, in antral follicles, the presence of FGF-10 is associated with increased follicular atresia, which matches its anti-estrogenic action. Discussion: From this review, we can conclude that FGF-10 is an important regulator of female reproduction. This growth factor acts in follicle survival, oocyte maturation, expansion of cumulus cells and proliferation of granulosa/theca cellsthrough direct and/or indirect actions in the control of folliculogenesis. Furthermore, FGF-10 seemed to have different effects throughout the follicular development. However, it is necessary to perform additional studies that may provide a better understanding about the importance of FGF-10 during folicullogenesis.
Structural characterization of the fibroblast growth factor-10 (FGF-10) and its role in ovarian follicular physiology
Keywords: FGF-10; Follicles; Ovary; Signal transduction